Analisis Penerapan Good Governance, Standar Akuntansi Pemerintahan, dan Sistem Akuntansi Instansi Terhadap Kualitas Laporan Keuangan - Roisatul Aminy; Endar Pituringsih; Erna Widiastuty (Valid: Jurnal Ilmiah, 2021)
The aims of this research is to find empirical evidence of the influence of good governance, accounting standards of government and agency accounting systems on the quality of the financial statements at the General Election Commission (KPU) in NTB. The unit of analysis used in this study is the entity, so that the population in this study is the whole members/staffs who are directly involved in the preparation of financial statements as many as 100 respondents. Processing data using Partial Least Square (PLS) with the analysis of second order construct. The results showed that the quality of financial reporting is affected by the application of accounting standards and accounting system of government agencies, but is not affected by the application of good governance. The implications of this research that the quality of financial statements prepared in accordance with accounting standards and government agencies use the accounting system through the integrated application system. These quality of financial statements present the financial information is relevant, reliable, comparable and understandable making it useful as a basis for decision making, and can be used as a reference for the work units in the area KPU NTB to achieve WTP opinion of BPK.